Upaya Peningkatan Hasil Belajar Pendidikan Pancasila Melalui Model Pembelajaran Discovery Learning Siswa Kelas 1 SD Negeri 2 Brangkal Tahun Pelajaran 2023/2024 - Elisabeth Aska Apriliana; Sri Suwartini; Isna Rahmawati (International Forum of Researchers and Lecturers, 2025)
This research aims to improve the learning outcomes of grade 1 students at SD Negeri 2 Brangkal using the Discovery Learning learning model in the Pancasila Education subject. This research is divided into two images, where each cycle consists of four research stages, namely: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. This research was conducted over a period of 3 months starting from February to April 2024. In this research the researcher acted as an observer by involving the class I Pancasila Education maple teacher as a colleague/collaborator. This Classroom Action Research (PTK) uses the Kemmis & Mc Taggart model. This research was carried out in two cycles where each cycle was held in one meeting. The subjects of this research were 18 grade 1 students at SD Negeri 2 Brangkal. Data collection techniques through evaluation tests, observation and documentation. The research results show that: (1) students become more active in learning activities. (2) there was an increase in Pancasila Education learning outcomes for grade 1 students at SD Negeri 2 Brangkal. This increase was proven by the results of the pre-cycle test, the average class score was 66.22, then it increased in cycle I to 82.5 and increased again in cycle II to 90.5. The percentage of completeness of learning outcomes in the pre-cycle was 40%, in cycle I was 75%, and in cycle II was 94% which achieved a KKTP ≥ 75. From the results of the above research it can be concluded that by implementing the Discovery Learning learning model it can improve learning outcomes in students. Pancasila education lesson for grade 1 students at SD Negeri 2 Brangkal.